2021
DOI: 10.1186/s13014-021-01877-4
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic ablative body radiotherapy boost for cervical cancer when brachytherapy boost is not feasible

Abstract: Background The purpose of this study was to analyze the treatment efficacy and safety of stereotactic ablative body radiotherapy (SABR) boost for cervical cancer patients not amenable to brachytherapy. Methods A retrospective review of the medical records from single institution of 25 eligible patients was performed. The patients underwent pelvic radiotherapy (RT) in 25 or 28 fractions with a median dose of 45 Gy (range 44–50.4 Gy). SABR boost was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In the CK-CTV plan, the HR-PTV was equal to the HR-CTV of the BT plan. Considering the setup and systematic error in EBRT and tumor motion, previous studies indicated that the margin of planning target volume (PTV) from the HR-CTV was 5 mm in LACC [ 9 , 13 , 17 ]. Hence, the HR-PTV was built from the HR-CTV of the BT plan with a margin of 5 mm in the CK-PTV plan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CK-CTV plan, the HR-PTV was equal to the HR-CTV of the BT plan. Considering the setup and systematic error in EBRT and tumor motion, previous studies indicated that the margin of planning target volume (PTV) from the HR-CTV was 5 mm in LACC [ 9 , 13 , 17 ]. Hence, the HR-PTV was built from the HR-CTV of the BT plan with a margin of 5 mm in the CK-PTV plan.…”
Section: Methodsmentioning
confidence: 99%
“…With the advent of radiation delivery and image-guiding techniques, stereotactic body radiotherapy (SBRT) can now deliver a substantially higher dose to defined target volumes and effectively protect organs at risk (OARs). In addition, compared with other EBRT boost techniques, a higher biologically equivalent dose can be achieved by SBRT [ 9 ]. Earlier studies indicated that SBRT could be similar to BT in clinical outcomes and minimal toxicities for patients with cervical cancer [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been few studies that have reviewed outcomes of patients who received SBRT boost in lieu of brachytherapy boost for a primary gynecologic malignancy (Table 1). A retrospective study including 25 patients with newly diagnosed cervical cancer treated with external beam radiotherapy followed by SBRT boost reported a 3-year local control rate of 80.9% with 20% of patients experiencing grade 3 toxicity including hematuria and hematochezia 4. Patients included in this analysis were unable to undergo brachytherapy boost due to either anatomic issues (ie, narrow vagina or cervical stenosis), tumor size felt to be too large for adequate brachytherapy dose distribution, morbid obesity, or other medical co-morbidities precluding brachytherapy.…”
Section: Sbrt In the Management Of Primary And Locally Recurrent Diseasementioning
confidence: 99%
“…A retrospective study including 25 patients with newly diagnosed cervical cancer treated with external beam radiotherapy followed by SBRT boost reported a 3-year local control rate of 80.9% with 20% of patients experiencing grade 3 toxicity including hematuria and hematochezia. 4 Patients included in this analysis were unable to undergo brachytherapy boost due to either anatomic issues (ie, narrow vagina or cervical stenosis), tumor size felt to be too large for adequate brachytherapy dose distribution, morbid obesity, or other medical co-morbidities precluding brachytherapy. The authors of this study conclude that although SBRT may not replace brachytherapy, SBRT may be a reasonable alternative if a patient is unsuitable for brachytherapy or if the procedure is not available.…”
Section: Sbrt In the Management Of Primary And Locally Recurrent Diseasementioning
confidence: 99%
“…Brachytherapy is essential for better treatment outcomes of locally advanced cervical cancer [ 1 ]. Even the recently developed external beam radiation therapy (EBRT) technique cannot substitute brachytherapy [ 2 ]. A significant advancement of gynecologic brachytherapy is utilization of three-dimensional (3D) images such as computerized tomography (CT) and magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%